Evaluation of factors affecting professional services in building projects in Nigeria - Aluko, Ralph Olusola; ldoro, Godwin (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study is aimed at investigating the main factors affecting professional services in the building industry towards achieving improvement of service delivery by consultancy firms. Questionnaires were distributed to 120(one hundred and twenty (120) respondents to elicit information about their perceptions of the factors affecting professional services. A total of 9 main factors and 39 sub-variables were used to design the questionnaire. The respondents were chosen based on their involvement in an on-going building projects. Therefore, purposive sampling was used to select the population of the study. One hundred and six (106) questionnaires were returned for analysis. The Mean Item Score(MS) was used to rank the factors as perceived by architects, engineers and quantity surveyors. The spearman rank order was calculated and used to test the hypothesis which states that there is no significant difference between the perceptions of the different group of professionals. The results showed that there is an agreement in the ranking with a strong relationship among the professionals. Ability of the client to choose the right design team is the most important factor in delivering quality service. Other important factors are staff motivation and training, commitment of members of staff of the design team, long term potential relationship with client organization, adequate authority for the design team to perform effectively and the client’s financial position. The result will guide both client and practitioners about those factors that need to be focused to improve service delivery.